2014
DOI: 10.1139/cjfas-2013-0558
|View full text |Cite
|
Sign up to set email alerts
|

Fish behavioral types and their ecological consequences

Abstract: Fish have proven to be model organisms for the study of animal personalities, and a rich literature documents consistent interindividual behavioral differences in a variety of species. However, relatively few studies have examined the ecological consequences of such consistent interindividual differences in behaviors in fish or other organisms, especially under field conditions. In this review and perspective, we discuss the factors that may lead to the formation and maintenance of behavioral types in fish pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
173
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(180 citation statements)
references
References 159 publications
5
173
2
Order By: Relevance
“…Studies of nonhuman animals have shown that personality traits are ubiquitous in the animal kingdom; a wide range of fish (Mittelbach, Ballew, & Kjelvik, 2014;Toms, Echevarria, & Jouandot, 2010), birds (e.g., chickens, Gallus gallus domesticus, Favati, Leimar, & Lovlie, 2014; zebra finches, Taeniopygia guttata, David, Auclair, & Cezilly, 2011, Schuett, Dall, & Royle, 2011Japanese quail, Coturnix japonica, Miller, Garner, & Mench, 2006), numerous mammal species (e.g., pigs, Sus domesticus, Marino & Colvin, 2015;horses, Equus caballus, Hausberger, Bruderer, Le Scolan, & Pierre, 2004;dogs, Canis familiaris, Svartberg, Tapper, Temrin, Radesäter, & Thorman, 2005;cats, Felis catus, Bennett, Rutter, Woodhead, & Howell, 2017;nonhuman primates, Freeman & Gosling, 2010); reptiles and amphibians (Allard, Fuller,Torgerson-White, & Murray, 2015;Burghardt, 2013), and invertebrates (Kralj-Fišer & Schuett, 2014, for a review) show persistent individual differences that can be organized along core personality dimensions, many of which overlap with those found in humans (Gosling, 2008;Gosling & John, 1999). Vonk, Weiss, and Kuczaj (2017) offer a comprehensive and upto-date review of personality in nonhuman animals.…”
Section: Personalitymentioning
confidence: 99%
“…Studies of nonhuman animals have shown that personality traits are ubiquitous in the animal kingdom; a wide range of fish (Mittelbach, Ballew, & Kjelvik, 2014;Toms, Echevarria, & Jouandot, 2010), birds (e.g., chickens, Gallus gallus domesticus, Favati, Leimar, & Lovlie, 2014; zebra finches, Taeniopygia guttata, David, Auclair, & Cezilly, 2011, Schuett, Dall, & Royle, 2011Japanese quail, Coturnix japonica, Miller, Garner, & Mench, 2006), numerous mammal species (e.g., pigs, Sus domesticus, Marino & Colvin, 2015;horses, Equus caballus, Hausberger, Bruderer, Le Scolan, & Pierre, 2004;dogs, Canis familiaris, Svartberg, Tapper, Temrin, Radesäter, & Thorman, 2005;cats, Felis catus, Bennett, Rutter, Woodhead, & Howell, 2017;nonhuman primates, Freeman & Gosling, 2010); reptiles and amphibians (Allard, Fuller,Torgerson-White, & Murray, 2015;Burghardt, 2013), and invertebrates (Kralj-Fišer & Schuett, 2014, for a review) show persistent individual differences that can be organized along core personality dimensions, many of which overlap with those found in humans (Gosling, 2008;Gosling & John, 1999). Vonk, Weiss, and Kuczaj (2017) offer a comprehensive and upto-date review of personality in nonhuman animals.…”
Section: Personalitymentioning
confidence: 99%
“…consistent behavioural differences among individuals across time and different contexts, have been of high interest among behavioural ecologists during the last decade (Sih et al 2004;Réale et al 2010;Stamps and Groothuis 2010;Mittelbach et al 2014). Recently, they have also received increasing attention in applied contexts, such as among studies on harvesting-induced evolutionary changes (Wilson et al 2011;Binder et al 2012;Härkönen et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…A plethora of recent studies has revealed that fishes indeed reveal less plasticity in their behaviors than previously believed, forming stable among-individual differences in 144 behavioral types (Conrad et al 2011;Mittelbach et al 2014). One of the key personality traits in animals in general is boldness (Réale et al 2007), which is often correlated with 146 other personality traits such as aggression, exploration, sociability or activity, thereby 8 creating behavioral syndromes (Sih et al 2004).…”
mentioning
confidence: 99%